PEDAGOGICAL SUPPORT OF COMPULSORY MEASURES OF EDUCATIONAL INFLUENCE ON JUVENILE DELINQUENTS - Kazakova, Tatyana; Vassilyeva, Irina; Varlamova, Olga; Vorobyov, Yuri; Dazmarova, Tatyana; Zakopyrin, Vladimir (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
The article presents the results of an empirical study. The aim of the study is to increase the effectiveness of compulsory measures for juvenile delinquents through the development and implementation of the pedagogical support system of these measures.The urgency of the research is determined by the lack of the scientific and methodological support for the practical implementation of compulsory measures of educational influence on juvenile delinquents; by the low level of the psychological and pedagogical readiness of the subjects of the pedagogical interaction; insufficiency of the pedagogical support as the most important condition of these measures effectiveness. Research methods are pedagogical analysis and synthesis, induction and deduction, comparison and generalization of research results, questionnaires, interviews, individual and group conversations, observation, generalization of independent characteristics, statistical methods of information processing.According to the research aim the system of the pedagogical support of compulsory measures of educational influence on juvenile offenders was developed and tested. It includes organizational and substantial, technological and staff resource components and their interaction, the main directions and ways for increasing of the pedagogical training level of the subjects of the pedagogical interaction. The results of the investigation proved the effectiveness of the pedagogical support system of compulsory measures for juvenile delinquents.